Stability analysis of slope in soil with strength mobilization. Issue 1 (February 2021) - Li, Xingyue; Fu, Shihao; Chen, Jiangong
Abstract: Considering the strength parameters cohesion c and internal friction angle < of the soil constitutive model are mobilized non-simultaneously. By gradually applying uniform vertical loads on the top of the slope, the progressive failure process of the slope is simulated by the FLAC 3D software. The failure state of the slope is judged by monitoring the maximum unbalance force in the slope system, and the slope sliding surface is determined based on the maximum shear strain increment, and the safety factor is calculated by the slope critical height ratio method. The numerical simulation shows that when the strength parameters are not synchronicity come into play, the safety factor is less than that of two cases, which consider the synchronous mobilization of strength parameters and the traditional Strength Reduction Method (SRM). Finally, the influence of residual cohesion and plastic strain threshold on the position of sliding surface and safety factor are discussed by numerical analysis.